Microstructural transition in monotectic alloys: A phase-field study. (October 2020) - Laxmipathy, V. Pavan; Wang, Fei; Selzer, Michael; Nestler, Britta
Highlights: A continuous and aligned monotectic structure translates into a droplet microstructure at high solidification velocities. A synchronous combination of the oscillations at the solid–liquid interface and a post-solidification oscillatory effect behind the growth front influence the microstructure formation. The role of inter-phase spacing is studied via the Jackson and Hunt relationship. Abstract: In the present study, we employ a multiphase-field model based on the grand chemical potential formulation to simulate the microstructural transition in a binary FeSn monotectic alloy. In a directional solidification environment, we systematically investigate the formation of monotectic microstructures. At equilibrium monotectic composition, we observe that depending on the imposed temperature gradient and the solidification velocity, the liquid L2 phase transforms into an array of droplets embedded in the solid phase matrix. Initiated at the solidification front, the minor liquid phase undergoes detachment and spherodization to form L2 droplets as a result of post-solidification ripening behind the growth front. We show that the wavelength of the oscillating phase is critical to observe a lamellar to droplet transition. A microstructural selection map at various growth conditions is delineated to illustrate the different monotectic microstructures. The present phase-field simulations, while providing significant insights into the formation of microstructures closes the gap with the in-situ observations reported earlier. In addition, the influence of lamellar spacing is investigated in detail through the Jackson and Hunt analytical relationship for the present material system.